Identifying parameters for a performance-based framework: Towards prioritising underutilised historical buildings for adaptive reuse in New Zealand. (July 2020) - Aigwi, Itohan Esther; Ingham, Jason; Phipps, Robyn; Filippova, Olga
Abstract: This paper identifies the parameters for a performance-based framework to prioritise underutilised historical buildings for adaptive reuse interventions, while discussing its effectiveness towards promoting sustainable and resilient urban areas in New Zealand. A narrative review of extant literature is done to justify the need for the performance-based framework and build a list of relevant parameters that elucidates all or part of a typical decision-making process regarding the selection of historical buildings for adaptive reuse in New Zealand. Five main priority aspects with significant evaluation criteria that have been identified from this study are economic sustainability, built-heritage preservation, socio-cultural aspects, building usability, and regulatory aspects. This paper's originality pertains to the development of parameters for a performance-based framework that offers a basis for relevant adaptive reuse stakeholders to prioritise underutilised historical buildings while balancing their diverse objectives. Accordingly, the performance-based framework has been validated to justify the relevance of its applicability to the different outlined parameters, towards prioritising underutilised historical buildings for adaptive reuse in New Zealand. Highlights: This paper identifies the parameters for a performance-based framework to prioritise underutilised historical buildings for adaptive reuse interventions, while discussing its effectiveness towards promoting sustainable and resilient urban areas in New Zealand. A narrative review of extant literature is done to justify the need for the performance-based framework and build a list of relevant parameters. Five main priority aspects with significant evaluation criteria that have been identified from this study are economic sustainability, built-heritage preservation, socio-cultural aspects, building usability, and regulatory aspects. This paper's originality pertains to the development of parameters for a performance-based framework. The performance-based framework has been validated to justify the relevance of its applicability to the different outlined parameters, towards prioritising underutilised historical buildings for adaptive reuse in New Zealand.